MOTIVES FOR CHOOSING SUBJECTS OF EXACT SCIENCE IN GENERAL SCHOOL - Gesevičienė, Vilma; Mazėtis, Edmundas (Acta Paedagogica Vilnensia, 2015)
The choice of exact science subjects and their learning levels by the pupils of forms 11-12 of the Lithuanian general schools has not only an academic basis, but it is also one of the most important factors predetermining success in the career development in the future. The article overviews the priorities for choosing subjects and external as well as internal motives that predetermine them, examines the issues of self-reflection on choosing exact subjects, and analyses the links between the choice of exact subjects and the further professional learners’ career. The results of the research have showed that of all the subjects of exact sciences the learners are most positive about mathematics; thus, a great share of learners choose a higher mathematics learning level, while the subjects of physics and chemistry are chosen by significantly fewer learners. Learners in essence are positive about the possibility to choose subjects; however, a large share of them would change the subjects or would like to learn still at least one or more subjects additionally. The greatest influence on choosing the subjects of exact sciences is made by family members, relatives, acquaintances who are representatives of different professions, and the information by higher schools; however, higher schools should improve the dissemination of the information on the knowledge and abilities required for studies. Studies of social sciences remain most popular, although a pretty large share of learners choose study programmes of physical, biomedicine and technology sciences. Still the latter programmes are chosen by the learners whose achievements in exact sciences are not the best ones. The research results presented in the article could be of interest to specialists of the education process organisation of different levels, teachers, parents and learners themselves.
Keywords: subjects of exact and natural sciences; levels of learning subjects; choice of subjects; motivation for choosing subjects; self-reflection on the choice